An Energy-Efficient Collaborative Caching Scheme for 5G Wireless Network - Muhammad Furqan (IEEE Access, 2019)
CCN (Content-centric network) has emerged as a promising architecture for future 5G network due to its in-network caching capability and receiver-driven content retrieval paradigm. Recently, the explosive increase in energy consumption driven by the rapid growth of network traffic has become a fundamental issue in CCN and caused widespread academic concern. In this paper, we proposed an energy-efficient scheme for the future 5G network. The aim of our scheme is to minimize the energy consumption by considering some important constraints, including limited storage, content popularity, placement and access to contents. Our proposed scheme provides efficient utilization of hotspot cache, minimizing transportation cost by using Zipf and knapsack which ensure local availability of cache contents and minimizing energy consumption. Finally, simulation results reveal that our proposed scheme outperform in term of saving energy, the impact of content popularity, cache size, placement, and device-to-device communication.